Assessing the Geothermal Resource Potential of an Active Oil Field by Integrating a 3D Geological Model With the Hydro-Thermal Coupled Simulation - Huang, Yonghui; Cheng, Yuanzhi; Ren, Lu; Tian, Fei; Pan, Sheng; Wang, Ke; Wang, Jianwei; Dong, Yuexia; Kong, Yanlong (Frontiers in Earth Science, 2022)
Assessment of available geothermal resources in the deep oil field is important to the synergy exploitation of oil and geothermal resources. A revised volumetric approach is proposed in this work for evaluating deep geothermal potential in an active oilfield by integrating a 3D geological model into an hydro-thermal (HT) coupled numerical model. Based on the analysis of the geological data and geothermal conditions, a 3D geological model is established with respect to the study area, which is discretized into grids or elements represented in the geological model. An HT coupled numerical model was applied based on the static geological model to approximate the natural-state model of the geothermal reservoir, where the thermal distribution information can be extracted. Then the geothermal resource in each small grid element is calculated using a volumetric method, and the overall geothermal resource of the reservoirs can be obtained by making an integration over each element of the geological model. A further parametric study is carried out to investigate the influence of oil and gas saturation on the overall heat resources. The 3D geological model can provide detailed information on the reservoir volume, while the HT natural state numerical model addressed the temperature distribution in the reservoir by taking into account complex geological structure and contrast heterogeneity. Therefore, integrating the 3D geological modeling and HT numerical model into the geothermal resource assessment improved its accuracy and helped to identify the distribution map of the available geothermal resources, which indicate optimal locations for further development and utilization of the geothermal resources. Caofeidian new town, Jidong oil field serves as an example to depict the calculation workflow. The simulation results demonstrate in Caofeidian new town geothermal reservoir, the total amount of geothermal resource, using the proposed calculation method, is found to be 1.23e+18 J, and the total geothermal fluid volume is 8.97e+8 m3. Moreover, this approach clearly identifies the regions with the highest potential for geothermal resources. We believe this approach provides an alternative method for geothermal potential assessment in oilfields, which can be also applied globally.